2008
DOI: 10.1007/s00264-008-0606-z
|View full text |Cite
|
Sign up to set email alerts
|

Bristow-Latarjet procedure with specific instrumentation: study of 34 cases

Abstract: A Bristow-Latarjet procedure with specific instrumentation was performed for recurrent dislocation or subluxation of the glenohumeral joint in 34 patients. The procedure was performed through a subscapularis splitting approach with three specific instruments and a special screw. The clinical outcome was assessed by the Duplay and the Constant scores. Radiographic study was conducted on 23 patients and CT scan in 11 patients. Of the 27 patients interviewed 92% were satisfied. Of the 23 patients examined, 15 had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 15 publications
(21 reference statements)
2
26
1
1
Order By: Relevance
“…Study details including patient demographics, follow-up characteristics and details of previous surgery are presented in Table I. These 30 studies described the results of 1658 open coracoid transfer procedures for shoulder instability. Three percent of cases (20 of 636) from 14 studies 1,5,6,9,13,[15][16][17]19,22,24,32,41,45 were revision procedures. Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Study details including patient demographics, follow-up characteristics and details of previous surgery are presented in Table I. These 30 studies described the results of 1658 open coracoid transfer procedures for shoulder instability. Three percent of cases (20 of 636) from 14 studies 1,5,6,9,13,[15][16][17]19,22,24,32,41,45 were revision procedures. Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen studies 4,12,29,31,33,36,39,[43][44][45]47,[49][50][51][52][53] (1058 cases) made no comment regarding whether the procedures were primary or revision cases. Metallic screw fixation was used in 29 studies, 1,[4][5][6]9,12,13,[15][16][17]19,22,24,29,[31][32][33]36,[42][43][44][45][46][47][49][50][51][52][53] and bioabsorbable screws and plugs were used in 1 study. 39 Repeat surgery was documented in 81 cases (4.9 AE 1.0%), including for hardware problems in 50 and recurrent instability in 20.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The procedure can be performed open [6,7] or arthroscopically [8,9]. Only a few studies with a large sample size have reported longterm outcomes [10][11][12][13], and only one has focused on dislocation arthropathy as defined by Samilson, which can occur after either shoulder dislocation or surgical repair [14].…”
Section: Introductionmentioning
confidence: 99%